Determinants of School Health Unit Program Implementation in Junior High Schools of Boyolali District, Indonesia - Umaroh, Ayu Khoirotul; Setiyadi, Noor Alis; Werdani, Kusuma Estu; Kusumaningrum, Tanjung Anitasari Indah; Setiyo Nugroho, Purwo (UI Scholars Hub, 2025)
Adolescent health problems such as stunting, attempted suicide, and tobacco use in Indonesia require attention. To address these challenges, the School Health Unit Program, a school-based health initiative, aims to improve student health and academic achievement. This study examined the relationship between human resources, teachers’ knowledge, facilities and infrastructure, financial resources, and the planning process for implementing the School Health Unit Program in junior high schools in Boyolali District, Indonesia. A cross-sectional design was utilized, involving 50 junior high school teachers responsible for the School Health Unit as respondents, with data collected through structured questionnaires. Multivariate logistic regression analysis revealed that financial resources (p-value = 0.001; Exp(B) = 12.93; CI = 2.878–58.060) and teachers’ knowledge (p-value = 0.028; Exp(B) = 6.67; CI = 1.230–36.117) were related to School Health Unit implementation. Schools with poor financial resources were over 12 times more likely, and teachers with a poor level of knowledge were approximately 6 times more likely, to implement the School Health Unit Program suboptimally. It is recommended that teachers participate in training programs, effective financial planning, and resource management to improve their capacity to manage the program more effectively.